The Relationship Among Intestinal Bacteria, Vitamin K and Response of Vitamin K Antagonist: A Review of Evidence and Potential Mechanism - Yan, Han; Chen, Yi; Zhu, Hong; Huang, Wei-Hua; Cai, Xin-He; Li, Dan; Lv, Ya-Juan; Si-Zhao,; Zhou, Hong-Hao; Luo, Fan-Yan; Zhang, Wei; Li, Xi (Frontiers in Medicine, 2022)
Vitamin K antagonist are commonly prescribed and effective oral anticoagulants with a narrow therapeutic range, and the dose requirements for different patients varied greatly. In recent years, studies on human intestinal microbiome have provided many valuable insights in disease development and drug reactions. A lot of studies indicated the potential relationship between microbiome and vitamin K antagonist. Vitamin K is absorbed by the gut, and the intestinal bacteria is a major source of vitamin K in human body. A combined use of vitamin K antagonist and antibiotics may result in an increase in INR, thus elevating the risk of bleeding, while vitamin K supplementation can improve stability of anticoagulation for oral vitamin K antagonist treatment. Recently, how intestinal bacteria affect the response of vitamin K antagonist remains unclear. In this review, we reviewed the research focusing on the physiology of vitamin K in the anticoagulation treatment, and investigated the potential pathways of intestinal bacteria affecting the reaction of vitamin K antagonist.